2003
DOI: 10.1002/jemt.10323
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome assembly in yeast

Abstract: Peroxisomes are essential organelles that may be involved in various functions, dependent on organism, cell type, developmental stage of the cell, and the environment. Until recently, peroxisomes were viewed as a class of static organelles that developed by growth and fission from pre-existing organelles. Recent observations have challenged this view by providing evidence that peroxisomes may be part of the endomembrane system and constitute a highly dynamic population of organelles that arises and is removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 126 publications
0
24
0
1
Order By: Relevance
“…The relationship of several of these gene products to the peroxisome was addressed by determining whether deletion influenced oleateinduced enhancement of Pex11-GFP expression. Numerous previous studies have shown oleate to cause a substantial induction in the size and/or number of Saccharomyces peroxisomes (Veenhuis et al 2003). Oleateinduced expression of PEX11 and the other PEX genes depends on Oaf1 and Pip2, transcription factors that bind as a heterodimer to the oleate-responsive element (Luo et al 1996;Rottensteiner et al 1996;Karpichev and Small 1998).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The relationship of several of these gene products to the peroxisome was addressed by determining whether deletion influenced oleateinduced enhancement of Pex11-GFP expression. Numerous previous studies have shown oleate to cause a substantial induction in the size and/or number of Saccharomyces peroxisomes (Veenhuis et al 2003). Oleateinduced expression of PEX11 and the other PEX genes depends on Oaf1 and Pip2, transcription factors that bind as a heterodimer to the oleate-responsive element (Luo et al 1996;Rottensteiner et al 1996;Karpichev and Small 1998).…”
Section: Resultsmentioning
confidence: 97%
“…Animals, by contrast, also perform b-oxidation in the mitochondrion using a separate set of enzymes (Bartlett and Eaton 2004). A variety of elegant methods using human cells, Saccharomyces cerevisiae, and other yeast species have identified 33 Pex proteins, or peroxins, that play a wide range of roles in peroxisome biogenesis and function (Purdue and Lazarow 2001;Eckert and Erdmann 2003;Veenhuis et al 2003;Moyersoen et al 2004). Most Pex proteins are highly conserved throughout eukaryotes; human disorders that result from mutations in any one of a number of pex genes have been studied extensively (Eckert and Erdmann 2003).…”
mentioning
confidence: 99%
“…For initiation of pexophagy, peroxisomes require a specific tag on the organelle, which serves as a target for the sequestering membrane. In methylotrophic yeast, the peroxisomal membrane-bound peroxins Pex14 and Pex3 play a role in initiation of macropexophagy (Bellu et al,2002;Bellu et al,2002;Veenhuis et al,2003). Pex14 is involved in the import of matrix proteins into peroxisomes.…”
Section: Mechanism Of Peroxisome Targeting For Degradationmentioning
confidence: 99%
“…Nevertheless, they constitute an important, metabolically plastic, and diverse complement to other common organelles within virtually all eukaryotic cell types (Subramani, 1998;Veenhuis et al, 2000;Parsons et al, 2001;Baker and Graham, 2002). A unique feature of this organelle's functional plasticity, which is more prevalent for plant (Kamada et al, 2003;Reumann, 2004) than other (Emanuelsson et al, 2003) peroxisomes, is that constitutive and induced changes in metabolic capabilities are accomplished exclusively via regulated posttranslational acquisitions of nuclearencoded matrix and membrane proteins (Mullen, 2002;Sparkes and Baker, 2002;Trelease, 2002;Lazarow, 2003;Veenhuis et al, 2003). Hence, targeting, intracellular sorting, and import of these proteins are critically important features for biogenesis/differentiation of peroxisomes in all organisms.…”
mentioning
confidence: 99%